2003
DOI: 10.1242/jcs.00600
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin signaling through the calreticulin/LDL receptor-related protein co-complex stimulates random and directed cell migration

Abstract: The matricellular extracellular matrix protein thrombospondin-1 (TSP1)stimulates focal adhesion disassembly through a sequence (known as the hep I peptide) in its heparin-binding domain. This mediates signaling through a receptor co-complex involving calreticulin and low-density lipoprotein (LDL)receptor-related protein (LRP). We postulate that this transition to an intermediate adhesive state enhances cellular responses to dynamic environmental conditions. Since cell adhesion dynamics affect cell motility,we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(167 citation statements)
references
References 50 publications
2
162
0
1
Order By: Relevance
“…Consistent with this, increased focal adhesion formation in FAK knockout fibroblasts results in impaired cell migration, whereas focal adhesion disassembly, such as that stimulated by TSP1/hep I, promotes cell migration (31,57). In addition to the obvious effects on cell motility, transition to the intermediate adhesive state could have profound effects on cell cycle progression, cell survival, and gene expression.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Consistent with this, increased focal adhesion formation in FAK knockout fibroblasts results in impaired cell migration, whereas focal adhesion disassembly, such as that stimulated by TSP1/hep I, promotes cell migration (31,57). In addition to the obvious effects on cell motility, transition to the intermediate adhesive state could have profound effects on cell cycle progression, cell survival, and gene expression.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, analysis of individual phosphorylation sites suggests that TSP1/hep I binding to calreticulin induces a transient increase in FAK kinase activity and a sustained increase in FAK signaling to downstream pathways. culminating in focal adhesion disassembly and increased cell migration (41,42,57). To determine the role of FAK phosphorylation in this pathway, we selectively inhibited these signals and observed the effect on hep I-induced FAK phosphorylation.…”
Section: Fak Is Required For Tsp1/hep I-induced Focal Adhesionmentioning
confidence: 99%
“…From the cell surface, CRT signals multiple cellular processes, including apoptotic clearance of cells, focal adhesion turnover, proliferation, migration, and anoikis resistance (4, 13, 20, 30 -33). Many of these responses to cell surface CRT are mediated by CRT binding to LRP1 (low density lipoprotein receptor-related protein 1) (13,(33)(34)(35).…”
mentioning
confidence: 99%
“…However, the process of angiogenesis is an inherently slow process (estimates range from 100 mm to 1 mm per day (Mikos et al, 1993;Orr et al, 2003)), and the timely generation of a stable vascular network has long been identified as a fundamental challenge for tissue engineering (Koike et al, 2004). Because of the inherent constraints of vascular ingrowth, constructs of clinically relevant size may progressively become devoid of oxygen and nutrients in their centre upon implantation, which will be detrimental for cellular function and survival (Radisic et al, 2006;Scheufler et al, 2008).…”
Section: Hypoxia In Bone Tissue Engineeringmentioning
confidence: 99%